Actualidad Asia (2017)
Within this section you will find a wide variety of articles, some of which were made by the student members of the hotbed of research in Asia Pacific of EAFIT University. These are: China, GDP growth, trade, competitiveness and seaports, carried out by Professor Ángel Licona Michel of the University of Colima Mexico; What is going to happen in the relations between China and the U.S. in the wake of President Trump's rise to power and the current situation ?, conducted by student Catalina Escobar of EAFIT University; Analysis of the economic growth of Singapore in the period 1970-2016: a development model for the international community, carried out by the students: Sara Catalina Mesa, María Alejandra Villa, Juanita Sánchez and Luis Miguel González of EAFIT University; three book reviews by some students belonging to the hotbed: Aurora Echeverri - "Mambrú", Sara Catalina Mesa - "The buried giant", María Alejandra Villa - "An event"; a section on Asia Pacific Fairs, conducted by student Lina Marcela Restrepo; a special of the main news of the radio program Asia Pacific Contact of the 2017-1 semester; and finally, a small introduction to the Japanese language, by Juan Pablo Abad, a student at EAFIT University.